2021
DOI: 10.1101/2021.05.10.21256529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity assessment of single dose Oxford–AstraZeneca vaccinated individuals infected with SARS CoV-2 in the Southeast Bangladesh

Abstract: The present global endeavor to uncover the most effective vaccines against severe acute respiratory syndrome coronavirus (SARS-CoV-2) that can tremendously prevent transmission, infection and significantly reduce public health risk. COVID-19 vaccination program is underway in different parts of the world including Bangladesh but till to date there is no available health data revealed among the vaccinated peoples. We conducted a cross-sectional study from February 15 to April 15, 2021 to assess the health statu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The CT severity score has been designed to assess the severity of COVID 19 pneumonia, in patients infected by the SARS-CoV-2 virus. Studies have shown that the use of vaccination reduces the clinical severity of infection by the corona virus even though it might not prevent infection by the virus [4,5]. This has been reflected in the CT severity score of the vaccinated patients in our study.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The CT severity score has been designed to assess the severity of COVID 19 pneumonia, in patients infected by the SARS-CoV-2 virus. Studies have shown that the use of vaccination reduces the clinical severity of infection by the corona virus even though it might not prevent infection by the virus [4,5]. This has been reflected in the CT severity score of the vaccinated patients in our study.…”
Section: Introductionmentioning
confidence: 59%
“…Earlier studies have shown a reduction in the clinical severity and hospital admission rates in patients vaccinated against the virus [4,5]. An Indian study done by Atre et al, published in June 2022 also revealed lower mean CTSS in fully vaccinated cohort than in partially vaccinated and unvaccinated cohort.…”
Section: Discussionmentioning
confidence: 90%
“…The continuation of this study on those who received the second dose more than six months ago will provide an appropriate booster interval, risk population category, and overview of herd immunity. According to a recent study conducted in the greater Chattogram division it is evident that administering the first dose (Oxford-AstraZeneca) vaccine significantly reduces health risk during the COVID-19 infection phase [ 54 ]. So, it is evident that similar research is clamoring for justifications for booster administration.…”
Section: Discussionmentioning
confidence: 99%